DETERMINATION OF RESERVOIR CHARACTERISTIC BASED ON THE WELL COMPLETION TEST IN THE RL WELL - Rial Dwi Martasari; Fama Agri Lactuca (Journal of Green Science and Technology, 2020)
Well Completion Test is a testing activity undertaken to determine the depth of production zone and feed center depth as well as to calculate the estimated production capacity of a well. Well completion tests are performed on wells that have just been drilled by exploring the depth of the well, measuring pressure and temperature, water loss test and gross permeability test. As a result of exploring the RL well, the tool was placed at a depth of 2000 meters. Injectivity is done at different pump rates, pressure and liquid faces. The gross permeability test results obtained an injection of 202.22 lpm/ksc, an average specific capacity of 5.028 lpm/meter, transmissivity of 0.1208955 darcymeter and skin factor 3.33381. Next calculate the production estimation using the injection that has been converted and plot to the graph then obtained the result of the estimated potential production of a well that is 6,3 MW. After a well has completed a well completion test, the next step is to test the production for more accurate results, because of the well completion test itself the accuracy is only about 50% only, therefore the production test needs to be done for the results which in getting more accurate.